ESG e a tutela constitucional da sustentabilidade - Barreto, Rodrigo Moreno Paz (2021)
Environmental protection is a task given to the entire society by constitutional imposition. To everyone, the fundamental right to a well-balanced environment consistent with the dignity of the human person is guaranteed. Companies, in performing their duties, must foster sustainable development based on the Triple Bottom Line (TBL) pillars – the tripod of sustainability. In this scenario, ESG (Environmental, Social and Governance) emerges as a way to measure a company’s engagement level with environmental and social issues, generating financial value. Sustainability stamps verify companies’ positioning on a methodological basis. ESG may be a tool to control a company’s performance in pursuing the will expressed in the constitutional text guaranteeing environmental protection as well as the protection of the human person’s fundamental right to it.